How College Students’ Perceived Teachers’ Positive Leadership Enhances Their Creativity? The Mediating Role of Intrinsic Motivation - Wang, Na; Huang, Jian-Hao (Journal of Ecohumanism, 2024)
The development and cultivation of college students’ creativity is a crucial task of global higher education. Therefore, this study aims to explore the influence of college students’ perceived teachers’ positive leadership on creativity through the mediating role of intrinsic motivation from the perspective of cognitive evaluation theory. The data for this study were collected from 511 students in Chinese colleges. The results indicate that college students’ perceived teachers’ positive leadership has a significant positive impact on creativity. Moreover, intrinsic motivation partially mediates the relationship between college students’ perceived teachers’ positive leadership and creativity. The results of this study have vital implications for college administrators and teachers.